An Investigation of China‐U.S. Bilateral Trade and Exchange Rate Changes Using the Autoregressive Distributed Lag Model. Issue 2 (23rd February 2018) - Hurley, Dene T.; Papanikolaou, Nikolaos
Abstract : This paper examines how China's bilateral trade with the U.S. responds to exchange rate changes of the real Chinese yuan against the U.S. dollar using annual data covering the period 1985 to 2014. The short‐run dynamics of the China‐U.S. trade balance vs. the yuan's depreciation is examined through the S‐curve and J‐curve effects, and the long‐run relationship is established using the autoregressive distributed lag model. The paper found evidence of the S‐curve but not of the J‐curve in the short‐run although the J‐curve effect is found to be present in the long‐run. China's bilateral ratio of exports to imports with the U.S. is found to have an inelastic response to the yuan's exchange rate change against the U.S. dollar in the short‐run, but in the long‐run, it has the expected elastic response. Compared with the influence of the Yuan‐U.S. dollar exchange rate change and China's real income, U.S. real GDP has the largest impact on China‐U.S. bilateral trade relations in the long‐run. Additionally, the structural break in the data series in 2008 from the Great Recession had a small but significant short‐term effect on the bilateral trade between the two nations. Following an exchange rate shock, the deviation of China's trade ratio from its long‐run level takes less than 2 years to converge.